Codificadores Convolucionais AbelianosDOI: 10.14209/jcis.1998.1 - Pedraza Arpasi, Jorge; Palazzo Jr., Reginaldo (Journal of Communication and Information Systems, 2015)
In this paper we establish the necessary and sufficient conditions for the construction of Abelian convolutional encoders. We show that such encoders are controllable, complete and minimal, the latter via a state reduction procedure, and having the elementary convolutional encoders as a subclass. As a consequence of the fact that the Abelian convolutional encoders whose trellis section is isomorphic to a cyclic group are concontrollable, then an algorithm for the construction of controllable Abelian convolutional encoders whose trellis section is isomorphic to an Abelian group (not cyclic) is proposed having the group of input, the group of states, and the group of output binary k-tuples, n-k-tuples and n-tuples, respectively. Examples of elementary and Abelian convolutional encoders are presented.